ANALISIS FAKTOR PENYEBAB STRES TENAGA KESEHATAN DI MASA PANDEMI COVID-19: NARATIVE REVIEW - Katarina Sembiring; Subhannur Rahman; Rian Tasalim (CNJ: Caring Nursing Journal, 2022)
The Covid-19 outbreak has plagued the entire world, so the WHO has included this outbreak in the category of a pandemic. In Indonesia, the data on cases of positive Covid-19 patients on March 2, 2020 were 4,239,396 people. Losses caused by the pandemic such as physical and mental disorders. This disruption is not only for patients diagnosed as positive for Covid-19, health workers are also threatened with their physical and mental health. The purpose of this study was to analyze the factors that cause stress in health workers during the Covid-19 pandemic: Narrative Review. The database used is Google Scholar. In this literature search using keywords in the form of: "health workers" and "stress" and "Covid-19". The literature used is literature published from 2020 to 2021. There are various factors that can cause stress for health workers during a pandemic including opportunity factors, constraints factors, demand factors, workloads, negative perception factors about Covid-19, experience factors lack of work, worry factor about Covid-19, social support factor, fear factor, negative stigma factor, supporting facilities factor, patient emotional demand factor, emotional intelligence factor, sleep quality.